Views on HPV and HPV Vaccination: The Experience at a Federal Qualified Clinic in Puerto Rico - Colón-López, Vivian; Toro-Mejías, Lizbeth M. Del; Conde-Toro, Alexandra; Serra-Rivera, Michelle J; Martínez, Tania M; Rodríguez, Verónica; Ríos, Ana M; Berdiel, Luis; Villanueva, Héctor (Journal of health care for the poor and underserved, 2016)
The purpose of this study was to understand through a quantitative assessment, the views of HPV and HPV vaccination among parents of sons from a FQHC in PR. A self-administered questionnaire was given to a convenience sample of 200 parents of sons 9-17 years old. Nearly 30% of the parents reported that their sons had initiated the HPV vaccine regimen. Health care provider recommendation was significantly associated with vaccine initiation. Among parents of unvaccinated sons, the main reason for not getting the HPV vaccine was they did not know that boys were allowed to get the vaccine. Future efforts should focus on multilevel interventions aimed to increase knowledge as well as other modified behavioral determinants in parents of young males about HPV and the vaccine. Capacity building efforts should be targeted also to increase health providers' education and communication skills to promote HPV vaccination effectively.